(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
One of the most common infections in clinical practice is urinary tract infections (UTIs). Limiting unnecessary antibiotic use and improving clinical care for many patients will result from accurate diagnosis and evidence-based treatment of UTIs. Crops and urine tests are useful for the diagnosis of UTIs; however, it is necessary to keep in mind their disadvantages. Due to the fact that most non-pregnant patients with asymptomatic bacteriuria do not require antibiotics and may even be harmful when prescribed, it is extremely important to distinguish true UTI from asymptomatic bacteriuria. The scope of UTI syndromes, such as acute uncomplicated cystitis, pyelonephritis, prostatitis and catheter-associated UTIs, determines the choice of antibiotics and the duration of their administration. Treatment methods also depend on the patient’s immunosuppression and the characteristics of their genitourinary system. Therefore, patients with urological obstruction or patients receiving kidney transplantation may need a specialized management approach that includes working with various disciplines. Some preventive measures can be used for people prone to frequent UTIs, but there is often no universal method. Thus, urinary tract infection is very common among urology doctors. The frequency of this pathology does not decrease, despite the existing methods of diagnosis and treatment. There are conflicting opinions about the etiology and pathogenesis of the disease, early signs of diagnosis and risk factors.